Fabrication, pore structure and compressive behavior of anisotropic porous titanium for human trabecular bone implant applications. (June 2015) - Li, Fuping; Li, Jinshan; Xu, Guangsheng; Liu, Gejun; Kou, Hongchao; Zhou, Lian
Abstract: Porous titanium with average pore size of 100–650 μm and porosity of 30–70% was fabricated by diffusion bonding of titanium meshes. Pore structure was characterized by Micro-CT scan and SEM. Compressive behavior of porous titanium in the out-of-plane direction was studied. The effect of porosity and pore size on the compressive properties was also discussed based on the deformation mode. The results reveal that the fabrication process can control the porosity precisely. The average pore size of porous titanium can be tailored by adjusting the pore size of titanium meshes. The fabricated porous titanium possesses an anisotropic structure with square pores in the in-plane direction and elongated pores in the out-of-plane direction. The compressive Young׳s modulus and yield stress are in the range of 1–7.5 GPa and 10–110 MPa, respectively. The dominant compressive deformation mode is buckling of mesh wires, but some uncoordinated buckling is present in porous titanium with lower porosity. Relationship between compressive properties and porosity conforms well to the Gibson–Ashby model. The effect of pore size on compressive properties is fundamentally ascribed to the aspect ratio of titanium meshes. Porous titanium with 60–70% porosity has potential for trabecular bone implant applications. Graphical abstract: Highlights: Porous titanium with elongated pores was fabricated by diffusion bonding of meshes. The dominant compressive deformation mode is buckling. Young׳s modulus and yield stress can be tailored based on a Gibson–Ashby model. Effect of pore size on compressive properties is due to aspect ratio of mesh wires. Porous titanium has potential for human trabecular bone implants application.